Research on Credit Evaluation Indicator System of High-Tech SMEs: From the Social Capital Perspective - Zhihao Liang; Jinming Du; Ying Hua; Yanbo Si; Miao Li (Systems, 2023)
High-tech small- and medium-sized enterprises (SMEs) play an important role in the high-quality economic development in a country. Nevertheless, due to the difficulties banks or other financial institutions have in accurately assessing their credit levels, financing difficulties have become the biggest bottleneck restricting the progress of high-tech SMEs, and therefore, this paper aims to construct a credit evaluation indicator system of high-tech SMEs. Based on prior studies and the characteristics of high-tech SMEs, this paper constructs an indicator system from financial and nonfinancial dimensions, including 22 measurement indicators reflecting the operation status, development potential, quality, and competitiveness of an enterprise. Principal component analysis (PCA) and a Delphi-analytic hierarchy process (AHP) method are employed for the evaluation. This indicator system innovates from the social capital perspective, and by setting more novel nonfinancial indicators, the system achieves a more comprehensive evaluation of credit level. This paper also performs an empirical application using the data from 125 enterprises in the Beijing–Tianjin–Hebei region of China, and further performs an empirical study on the external environment’s impact on the credit level. The empirical results all show consistency with existing studies, verifying the workability and validity of the indicator system we constructed.